Problematizing markets: market failures and the government of collective concerns. Issue 2 (3rd April 2019) - Ossandón, José; Ureta, Sebastián
Abstract: Neoliberalism is usually associated with pro-market values. This paper argues that more attention should be paid to the specific forms of market criticisms that unfold in neoliberal settings. We adapt Foucault's and Callon's notion of problematization to study recent policy reforms in Chile. The analysis shows a transition from a set of policies justified in terms of the virtues of the market to policy interventions based on a comparison between the situation in the specific area and ideal well-functioning markets. This transition, we propose, signals a particular mode of governing with its characteristic cognitive operation (areas of collective concerns are assessed in terms of market failures), apparatus (policy instruments oriented to remediate market failures), and the jurisdiction of a particular type of experts.